Investigating the impact of a chronic disease self-management programme on depression and quality of life scores in an Irish sample. Issue 7 (9th August 2022) - Campbell, Dónal; Wilson O'Raghallaigh, Jennifer; O'Doherty, Veronica; Lunt, Victoria; Lowry, Damien; Mulhern, Sinead; Lonergan, Katie; McSharry, Kathy; Lynnott, Jackie; Forry, Mary; Evans, David; Pardoe, Peter; et al.
ABSTRACT: Depression is more common among people with chronic conditions than in the general population and can negatively influence both health behaviours and outcomes. The Chronic Disease Self-Management Programme (CDSMP) is a six-week psycho-educational programme designed to promote self-efficacy and to teach patients skills for managing their chronic conditions. A longitudinal design evaluated the effect of the CDSMP on depression in an Irish cohort. Self-report data on psychological wellbeing were collected at baseline (n = 263), immediately post-program (n = 102), and six months (n = 81) after enrolment. CDSMP participation was associated with a significant decrease in the mean depression score of the whole sample, across the three time points. Significant improvements in quality of life and health interference in social activities were also observed among those who met criteria for depression on the PHQ-8 at baseline, but not their peers with sub-threshold depression scores. Quality of life continued to improve between the end of the programme and 6-month follow-up. These findings support the efficacy of the CDSMP in the treatment of chronic conditions, as well as its role in promoting sustainable changes to quality of life.